The effect of psychological counseling program in improving the cognitive side of (hardness to flexibility) and learning some basic skills of basketball PreparationThe effect of psychological counseling program in improving the cognitive side of (hardness - Dr. Shatha Abdul-hafidh Ismaeil (الرياضة المعاصرة)
OBJECTIVE: To identify the effect of psychological counseling program on improving the cognitive side from rigidity to elasticity .